2008
DOI: 10.1111/j.1467-9523.2008.00461.x
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Power and Sustainability in Contemporary Rural Europe

Abstract: This article looks at the evidence given in the 'cognitive approach to rural sustainable development: the dynamics of expert and lay knowledge' research project of changing rural power relations in the context of sustainability and knowledge use in Europe. It explores what kinds of knowledge contribute to sustainable development in rural development projects and how they are created or empowered, according to the interest and capacity of the different actors involved. The article examines how actors interpret … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 20 publications
0
28
0
1
Order By: Relevance
“…The following discussion adopts a classification of knowledge as emerged in previous studies, in particular in Csurgò, Kovách, &Kuĉerová (2008) andFonte (2008). Local and scientific food knowledge, tourism knowledge, and local managerial and political knowledge are discussed, first individually and then focusing on their co-existence.…”
Section: Discussion: Knowledge In Food Tourismmentioning
confidence: 99%
See 2 more Smart Citations
“…The following discussion adopts a classification of knowledge as emerged in previous studies, in particular in Csurgò, Kovách, &Kuĉerová (2008) andFonte (2008). Local and scientific food knowledge, tourism knowledge, and local managerial and political knowledge are discussed, first individually and then focusing on their co-existence.…”
Section: Discussion: Knowledge In Food Tourismmentioning
confidence: 99%
“…Nevertheless, contributions that can be relevant for the study of food tourism in a knowledge perspective can be found in other fields of study. A useful classification of knowledge from Rural Studies distinguishes between scientific knowledge, political and managerial knowledge, and local knowledge (Csurgò, Kovách, & Kuĉerová, 2008;Fonte, 2008). Scientific knowledge is a standardised form of knowledge deriving from research, and in the case of food it regards gastronomy.…”
Section: Food Tourism In a Knowledge Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…What is needed for the promotion of effective local participation schemata and the organization of social consensus regarding natural resource management is power sharing between local people and experts (Arts & Buizer, 2009;Hovik et al, 2010). Unless this precondition is met, scientific experts will become so powerful in any type of deliberation process that local people or their interests will be excluded Lövbrand, 2009;Steffek, 2009) and the democratic legitimacy of the process will be severely undermined (Csurgó et al, 2008;Kleinschmit et al, 2009). An important barrier that has to be overcome in this respect is the restoration of trust between social actors with competing interests and powers.…”
Section: Can Forest Management In Protected Areas Produce New Risk Simentioning
confidence: 99%
“…A hagyományos, és végső soron minden esetben a foglalkozást figyelembe vevő egyenlőtlenség elemzések problematikusságára utal, hogy a szakma doyenjei sem publikáltak Kolosi Tamás Terhes babapiskóta című kötete (Kolosi 2000) után a teljes magyar társadalom egyenlőtlenségeire vonatkozó munkákat. A rétegződésről szóló alapkönyv szerzője, Ferge Zsuzsa saját maga tett több fontos kísérletet a rétegződési modell újraértelmezésére illetve az EGP modell kritikájára (Ferge 2002/b, 2006/b, 2008/b, . Tardos Róbert (2008 a foglalkozás alapú rétegződésvizsgálatok csökkenő magyarázó képességét annak tulajdonítja, hogy azok a foglalkozási kategóriákat rutinszerűen kezelik, miközben a hagyományosan alkalmazott kategóriák közül már több elveszítette tényleges kohéziós erejét.…”
unclassified